Solid Waste Generation and Management Techniques In Ado-Ekiti, South- West, Nigeria - Sola, Ogunleye, Olusesan; Sunny, Uzoma, Emmanuel (European Scientific Journal, ESJ, 2018)
Solid waste management is a contemporary issue and as such has attracted a lot of attention worldwide. In Nigeria today, the government and other relevant authorities seemed to be helpless in finding the best alternative measure to adopt in ameliorating the negative impact of wastes on the environment. It is on this note that this paper examined solid waste management techniques in Ado-Ekiti, South West, Nigeria. Data for the study were collected from both primary and secondary sources. The methodology for primary data collection were preliminary study, observation, and administration of questionnaires. 400 copies of questionnaire were administered on randomly selected respondents from five different zones in the study area. Secondary data were collected mainly from Ekiti State Waste Management Authority, National Bureau of Statistics as well as from GIS Spatial Nigeria Limited. Data were analysed using tables, frequencies and percentages, as well as Chi-square analysis. The hypothesis generated were tested at (p< 0.05) level of significance. It was discovered that there was a significant difference in the method of waste disposal adopted in the study area (χ2=3508.074, df=25, p<0.05). The study recommends a reduction in the cost of waste collection by the Waste Management Companies, this will encourage the people to make of their services thus giving the waste management companies a full control of waste collection and management resulting in sustainable waste management in the study area.